Combined detrital zircon fission track and U-Pb dating of the Late Paleozoic to Early Mesozoic sandstones in the Helanshan, western Ordos fold-thrust belt: Constraints for provenance and exhumation history. (October 2019) - Shi, Guanzhong; Soares, Cleber J.; Shen, Chuanbo; Wang, Hua; Yang, Chaoqun; Liang, Chao; Liu, Menghe
Abstract: In order to unravel the Mesozoic sedimentation in response to multistage deformation of the western Ordos fold-thrust belt, combined zircon U-Pb and fission track analyses of single zircon grain are conducted for seven sandstone samples in the Helanshan area. Zircon FT ages are calculated using absolute uranium concentration determined by LA-ICP-MS during the procedure of zircon U-Pb dating. The newly-obtained zircon FT data show age features that are comparable with the previous zircon FT ages obtained by conventional FT methods (by which uranium contents are determined through an external detector to map induced fission tracks). The newly-obtained zircon FT ages have four subordinate FT age peaks (i.e., 225 Ma, 165 Ma, 125 Ma and 80 Ma) which are well matched with the regional geodynamic events occurred in the Late Triassic, Late Jurassic, Late Cretaceous and Early Cenozoic, respectively; and the zircon U-Pb ages have two main peaks at the Paleoproterozoic and the Late Paleozoic. The zircon U-Pb ages, integrating with the FT ages and available paleocurrents, suggest that the Paleoproterozoic basement rocks and Late Paleozoic plutonic rocks of the Alxa Block are the source rocks for the Triassic sandstones, and the Jurassic sandstones are associated with a multi-cycling sedimentation. The Jurassic sandstones contain recycled zircons that firstly deposited in the Triassic strata and subsequently exhumed during the Late Triassic-Early Jurassic.